2019
DOI: 10.1177/1178646919834550
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Related Metabolic Perturbations of Gut Microbial Shikimate Pathway-Tryptamine-tRNA Aminoacylation-Protein Synthesis in Human Health and Disease

Abstract: Human gut bacterial Na(+)-transporting NADH:ubiquinone reductase (NQR) sequence is associated with Alzheimer disease (AD). Here, Alzheimer disease-associated sequence (ADAS) is further characterized in cultured spore-forming Clostridium sp. Tryptophan and NQR substrate ubiquinone have common precursor chorismate in microbial shikimate pathway. Tryptophan-derived tryptamine presents in human diet and gut microbiome. Tryptamine inhibits tryptophanyl-tRNA synthetase (TrpRS) with consequent neurodegeneration in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 146 publications
0
12
0
Order By: Relevance
“…The shikimate pathway was discovered to be the biosynthetic pathway present in plants and microorganisms that forms the aromatic acids phenylalanine, tyrosine and tryptophan via their precursor chorismate [ 26 ]. Mammals were considered to lack this pathway, but recent studies have indicated the formation of metabolites derived from the shikimate pathway by the gut microbiome [ 27 ]. The products of the shikimate pathway can give rise to indoles, which fulfill many functions in microbial communities, such as quorum sensing, intercellular communication and signaling pathways [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shikimate pathway was discovered to be the biosynthetic pathway present in plants and microorganisms that forms the aromatic acids phenylalanine, tyrosine and tryptophan via their precursor chorismate [ 26 ]. Mammals were considered to lack this pathway, but recent studies have indicated the formation of metabolites derived from the shikimate pathway by the gut microbiome [ 27 ]. The products of the shikimate pathway can give rise to indoles, which fulfill many functions in microbial communities, such as quorum sensing, intercellular communication and signaling pathways [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…HA is a well-known urinary metabolite of host-microbial origin. Its precursor benzoate is derived from the microbial degradation of polyphenols from the diet or synthesized via the shikimate pathway [ 27 , 31 ]. Chorismate can be converted directly into benzoate or with phenylalanine as an intermediate [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…By using a machine learning model with 20 blood parametric of 366 Covid-19 patients depicted severity of patients with a proteomic risk score and that correlated with gut microbiota, which resembles to pro-inflammatory cytokines [ 198 ]. Metabolomics analysis of some potent amino acid related pathways like aminoacyl-tRNA biosynthesis pathway, arginine biosynthesis pathway, valine, leucine and isoleucine biosynthesis pathways from fecal samples of 987 patients revealed a pattern that harmonized with disease extremity [ 199 ]. Hence, Gau et al predicted intestinal microbiota and associated metabolites may be used as further analysis and characterized as an indicator to forecast susceptibility of SARS-Cov-2 with an individual or entire population [ 200 ].…”
Section: Patient Profiling and Use As Diagnostic Markersmentioning
confidence: 99%
“…The shikimate pathway is found exclusively in microorganisms and plants and is mainly dedicated to the production of aromatic amino acids (phenylalanine, tyrosine, and tryptophan) in bacteria [77]. Evidence has also shown that perturbation in the shikimate pathway is diet-related [78].…”
Section: Functional Analysesmentioning
confidence: 99%